Toward a Universal Definition of Child Sexual Grooming. Issue 8 (3rd August 2022) - Winters, Georgia M.; Kaylor, Leah E.; Jeglic, Elizabeth L.
ABSTRACT: It is estimated that 30–45% of child sexual abusers use sexual grooming tactics. While sexual grooming is considered integral to the child sexual abuse process, there has yet to be a universally accepted definition of the construct that condenses and summarizes this complex process. Based upon a thorough evaluation and critique of prior definitions and research on a content validated model of sexual grooming, a new operational definition of sexual grooming is proposed. An easily understood and applied definition of sexual grooming is needed for measurement of the construct. Further, having a common language to describe sexual grooming is necessary for research, communication, detection, prevention, and intervention of child sexual abuse.